Implementasi Monitoring Dan Notifikasi Kualitas Udara Menggunakan Arduino Berbasis IoT - Muhamad Muzakirin; Ahmad Haidar Mirza (APTIKOM SUMSEL, 2022)
The results of this study are an IoT-based tool that can monitor air quality and data, the data. which is very influential on the health of those who inhale it, especially humans. By using sensors MQ7 and DHT11 where these sensors have their respective functions, MQ7 functions to detect CO gas (carbon monoxide) while DHT11 functions to detect temperature and humidity, which can know the air quality every day. In this study using the prototype method to build hardware later. To be able to provide accurate and precise information to users and the public to increase self-awareness in reducing air pollution levels. The first stage of this research is to collect data for 7 days in March 2022 in Penukal Abab Lematang Ilir Regency. Furthermore, the data that has been obtained the results are calculated using excel. The result of calculating the highest average value for CO is 9.99 ppm on March 7, 2022, at 16:41 and the lowest average value of 1.83 ppm on March 1, 2022, at 10:34. The average for the overall value is 3.37ppm, so it can be concluded that the air quality in Penukal Abab Lematang Ilir Regency is still identified as good.